New species in the treehopper genus Bocydium Latreille, with description of nymphal stages and observations on their natural history - Flórez-V, Camilo; Evangelista, Olivia (Zootaxa, 2017)
Six new species of Bocydium Latreille are described, and life history notes are provided based on field data from the Central and Western Cordilleras of the Colombian Andes. Information on host plants, treehopper-ant mutualisms, and behavior of adults and nymphs are provided for most newly discovered species (B. bilobum Flórez-V sp. nov., B. hadronotum Flórez-V sp. nov., B. mae Flórez-V sp. nov., B. sakakibarai Flórez-V sp. nov., B. sanmiguelense Flórez-V sp. nov., and B. tatamaense Flórez-V sp. nov.) in addition to two previously known species of Bocydium. A key to species of the genus is presented, along with photographs of primary type specimens for all species described by Dr. Albino M. Sakakibara. A nomenclatural change is proposed for B. cubitale Richter, 1954 syn. nov., herein considered junior synonym of B. bullife-rum Goding, 1930.